Diverse Localization and Protein Binding Abilities of Glyceraldehyde-3-Phosphate Dehydrogenase in Pathogenic Bacteria: The Key to its Multifunctionality - Kopeckova, Monika; Pavkova, Ivona; Stulik, Jiri (Frontiers in cellular and infection microbiology, 2020)
Bacterial proteins exhibiting two or more unrelated functions, referred to as moonlighting proteins, are suggested to contribute to full virulence manifestation in pathogens. An expanding number of published studies have revealed the glycolytic enzyme glyceraldehyde-3-phosphate dehydrogenase (GAPDH) to be a multitasking protein with virulence impact in a number of pathogenic bacteria. This protein can be detected on the bacterial surface or outside the bacterial cell, where it interacts with host proteins. In this way, GAPDH is able to modulate various pathogenic processes. Moreover, it has been shown to be involved in non-enzymatic processes inside the bacterial cell. In this mini review, we summarize main findings concerning the multiple localization and protein interactions of GAPDH derived from bacterial pathogens of humans. We also briefly discuss problems associated with using GAPDH as a vaccine antigen and endeavor to inspire further research to fill gaps in the existing knowledge.
Keywords: Humans; Proteins; glyceraldehyd-3-fosfátdehydrogenasy; Bacteria; Glyceraldehyde-3-Phosphate Dehydrogenases; Virulence; vazba proteinů; virulence; bakteriální proteiny; Bacterial Vaccines; Protein Binding; proteiny; Bacterial Infections; bakteriální infekce; lidé; Bacterial Proteins; bakteriální vakcíny